2013
DOI: 10.1021/jo400200v
|View full text |Cite
|
Sign up to set email alerts
|

Atropisomers of Arylmaleimides: Stereodynamics and Absolute Configuration

Abstract: 4-Aryl-3-bromo-N-benzylmaleimides and 3,4-biaryl-N-benzylmaleimides have been synthesized by a modified Suzuki cross-coupling reaction from 3,4-dibromo-N-benzylmaleimide. The conformational studies by dynamic NMR and DFT calculations showed that the interconversion barrier between the two available skewed conformations is under steric control. When the aryl group was a 2-methylnaphthyl, thermally stable atropisomers were isolated by enantioselective HPLC and their absolute configurations were assigned by TD-DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 82 publications
0
22
1
Order By: Relevance
“…We also performed a control experiment to see the possibility of path‐b, by performing the TRR of 1 bearing a C4‐cyclopropyl group (instead of aryl group) and found that it could not give the rearranged product under these conditions. To understand more about the atropisomerism of these compounds we have performed DFT calculations, because so far there is no report on the computational study of the TRR, though some reports devoted to study the atropisomersim . Single point energies and geometry optimizations were performed at the DFT level using the M062X functional and 6‐31G(d,p) basis functions.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed a control experiment to see the possibility of path‐b, by performing the TRR of 1 bearing a C4‐cyclopropyl group (instead of aryl group) and found that it could not give the rearranged product under these conditions. To understand more about the atropisomerism of these compounds we have performed DFT calculations, because so far there is no report on the computational study of the TRR, though some reports devoted to study the atropisomersim . Single point energies and geometry optimizations were performed at the DFT level using the M062X functional and 6‐31G(d,p) basis functions.…”
Section: Resultsmentioning
confidence: 99%
“…Several chiral compounds have an exchangeable hydrogen atom at the stereogenic center, and this can lead to enantiomer interconversion on a timescale that is incompatible with storage or dosing of a single enantiomer . There is another mechanism of enantiomer interconversion that takes place when the source of chirality is the hindered rotation around a stereogenic axis: in such cases, slow axial rotation generates atropisomers, i.e., stereoisomers with hindered internal motions such that the individual enantiomers or diastereoisomers have half‐lives long enough to allow their physical separation at room temperature (time scale in the minutes range) . Benzodiazepines are a well‐known class of sedatives, hypnotics, anxiolytics, and anticonvulsants.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] There is another mechanism of enantiomer interconversion that takes place when the source of chirality is the hindered rotation around a stereogenic axis: in such cases, slow axial rotation generates atropisomers, i.e., stereoisomers with hindered internal motions such that the individual enantiomers or diastereoisomers have half-lives long enough to allow their physical separation at room temperature (time scale in the minutes range). [6][7][8][9][10] Benzodiazepines are a well-known class of sedatives, hypnotics, anxiolytics, and anticonvulsants. Diazepam and other structurally related 1,4benzodiazepin-2-ones lacking a stereogenic center at C3 exist in the form of rapidly interconverting conformational enantiomers.…”
mentioning
confidence: 99%
“…61 Given the result of the preliminary tests, the 6-311++G(2d,p) basis set was employed for the calculations, as it is computationally cheaper than def2TZVPP and usually provides good accuracy. [61][62][63][64][65] The rotational strengths were calculated in both length and velocity representation, the resulting values being very similar (RMS difference < 5%).…”
Section: Absolute Configurationmentioning
confidence: 99%